The Unmaking of the Arab Intellectual Prophecy, Exile and the Nation - Halabi, Zeina (Edinburgh Studies in Modern Arabic Literature : ESMAL, 2022)
Examines the depiction of intellectuals in contemporary Arabic literatureZeina G. Halabi examines the unmaking of the intellectual as prophetic figure, national icon, and exile in Arabic literature and film from the 1990s onwards. She comparatively explores how contemporary writers and film directors such as Rabee Jaber, Rawi Hage, Rashid al-Daif, Seba al-Herz and Elia Suleiman have displaced the archetype of the intellectual as it appears in writings by Elias Khoury, Edward Said, Jurji Zaidan and Mahmoud Darwish. In so doing, Halabi identifies and theorises alternative articulations of political commitment, displacement, and loss in the wake of unfulfilled prophecies of emancipation and national liberation. The Unmaking of the Arab Intellectual offers critical tools to understand the evolving relations between aesthetics and politics in the alleged post-political era of Arabic literature and culture.Key FeaturesExamines the depiction of Arab intellectuals in post-1990s literatureOffers a new understanding of the political in the contemporary eraRe-reads the legacy of canonical modern Arab writersOffers critical tools to understand the contemporary eraRead a review by Michael Allan (University of Oregon)Listen to Zeina Halabi discuss the book on the Forum for Transregional Studien in Berlin blogMaydan interviews Zeina Halabi - read the full article Read a review in Arabic Literature